USING KWL STRATEGY TO ENHANCE READING COMPREHENSION ACHIEVEMENT AND CHARACTERS OF THE SEVENTH GRADE STUDENTS OF SMPN 1 BABAT SUPAT, MUSI BANYASIN - Mardiana Mardiana (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
Abstract: Teachers need a strategy in their instructional process to assist them develop both students’ skills and characters. KWL is one of alternative reading strategies that can be used by teachers to enhance the students’ reading skills characters. This study aimed at investigating the influence of KWL toward students’ reading comprehension achievement and five aspects of characters; (1) Motivating Oneself, (2) Self awareness, (3) Managing Emotion, (4) Emphaty, and (5) Social Skill. Seventy four seventh graders were selected as the sample and equally divided into experimental (N=37) and control groups (N=37), in which only the experimental group was given the treatment using the strategy. However, both groups were tested before and after the treatment. The results of paired sample t-test showed that there were significant improvement in students’ reading comprehension achievement. In addition, the experimental group outperformed the control group with a significant mean difference of 10.16 (p=.000) on reading comprehension. Furthermore, the result of modus showed improvement on  students’ characters and there were also found difference in each aspects of characters after they were taught by using KWL strategy. Hence, based on the results of this study, KWL strategy was effective to enhance the students’ reading comprehension and characters. Key words: Reading Comprehension, Characters, KWL strategy, seventh graders